What does work in education - Barrientos Mollo, Roberto (2016)
In an episode of the series "Charlie Brown", the protagonist bet his friends that he would teach him to speak to Snoopy, his dog. After a week, they approached and claimed the bet arguing that the pet had failed to speak. Charlie's response was quite assertive and clear: "I didn't say I was going to learn to speak. I only bet that I was going to teach him to speak, and that's what I did." This story depicts the education dilemma of the twentieth century. We have generated a system, an infrastructure and a scaffolding that guarantees teaching, but not learning. It is no secret to anyone that when we have completed the curricular program, or believed to comply, more and more students do not achieve what is expected. As Dufour, Eaker and Karhanek say in the twentieth century the constant has been the time and support that the educational system offered to each student and in the twenty-first century the constant will be to guarantee quality learning in all students (2010). That is, in the twentieth century the time that has been offered to learn is the same for everyone, under the assumption that all students are equal and learn at the same time, and the learning has been the variable (figure 1). For every 1,100 hours of teaching in the primary education system, only 26.6% of students achieve the expected in mathematics, as shown by the results of the recent evaluation of second grade students in 2015. The same number of support for each student and a wide variation in learning achievements. What must happen in the 21st century is that the constant is that 100% of the students learn versus the current 26.6%, but for that a structural change is needed about the time and support offered to each student. We have to change the chip and understand that maybe some students will need 1,800 hours and other types of support to reach that 100% achievement. This implies rethinking the system and working on the most effective practices in education. How to achieve it? There comes the creativity and innovation of all those interested in students really learning.